2017
DOI: 10.1080/13696998.2017.1363049
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare resource utilization and costs for patients with pulmonary arterial hypertension: real-world documentation of functional class

Abstract: Using administrative data to document disease severity, this study replicates and expands on findings obtained from the registry study; disease severity was associated with higher healthcare resource utilization and costs. Stakeholders' implications for patient management are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 17 publications
3
35
0
Order By: Relevance
“…The 5-year survival in patients with PAH ranges from 59 to 68% [3][4][5]. Various risk score calculators have been developed for predicting contemporary survival [6][7][8][9], and certain indicators, including B-type natriuretic peptide, N-terminal pro B-type natriuretic peptide, functional status, and 6-minute walk distance, are predictors of outcomes and survival [5,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The 5-year survival in patients with PAH ranges from 59 to 68% [3][4][5]. Various risk score calculators have been developed for predicting contemporary survival [6][7][8][9], and certain indicators, including B-type natriuretic peptide, N-terminal pro B-type natriuretic peptide, functional status, and 6-minute walk distance, are predictors of outcomes and survival [5,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Mean total health care costs for patients with PAH were higher than costs for a Centers for Medicare and Medicaid Services managed care control group and increased with more severe baseline FC, with patients in FC IV having the highest costs [6]. Health care resource utilization, including inpatient admissions, longer average lengths of stay, and emergency department visits, was also greater for patients with FC IV than other FC subgroups [6]. In another study, patients with severe PAH who received medical therapy alone were more likely to have more severe FC (III/IV), which was associated with greater health care resource utilization compared with patients who received exercise training plus medical therapy [53].…”
Section: Fc and Economic Outcomesmentioning
confidence: 80%
“…Mean total health care costs for patients with PAH were higher than costs for a Centers for Medicare and Medicaid Services managed care control group and increased with more severe baseline FC, with patients in FC IV having the highest costs [6]. Health care resource utilization, including inpatient admissions, longer average lengths of stay, and emergency department visits, was also greater for patients with FC IV than other FC subgroups [6].…”
Section: Fc and Economic Outcomesmentioning
confidence: 89%
See 1 more Smart Citation
“…14,23 A retrospective database study showed PAH (FC II-IV) patients had high healthcare resource utilization with annual pharmacy costs 17 to 21 times higher and medical costs 10 to 11 times higher than the average Medicare patient. 24 A prospective analysis of newly diagnosed PAH patients from REVEAL showed a substantial burden of disease with a 57% incidence of all-cause hospitalization (52% PAHrelated) and worse survival at 3 years. 25 Those charged with making managed care formulary decisions which optimize the care of patients and manage resources, are searching for ways to offset high costs.…”
mentioning
confidence: 99%